A Comparative Study of the Master's Program in Educational Administration in a Saudi University and Four Similar Programs in the United States - Saud G. Albeshir (Journal of Arts, Literature, Humanities and Social Sciences, 2022)
The current study aimed to compare the master's program in educational administration at King Saud University (KSU) and four master's programs in the same discipline at distinguished universities in the United States. This study compared the admission requirements for master's programs, study plans, curricula, and graduation requirements for a master's program in educational administration at KSU and master's programs in educational administration and leadership offered by the four American universities. The study attempted to discover the similarities and differences in the previously mentioned topics. The researcher found some likenesses between the master's program at KSU and the four American universities, such as the agreement on the efficiency and the qualification of students who plan to study in the master's programs and the significance of preparing students with the essential skills and school principals with the necessary knowledge, in addition to the similarity of many conditions for graduation and obtaining a master's degree. On the other hand, the research likewise found multiple dissimilarities between the master's program at KSU and those of the four American universities in many areas, including the following: There are many admission prerequisites for the master's program at KSU compared to the four American universities. Furthermore, there are differences in the number of units KSU students have to complete at KSU compared to the four American universities. It is also noted that students in the KSU educational administration program are obliged to complete scientific research to complete graduation requirements, while students in the four American universities enjoy other options that serve as partial fulfillment of the requirements for the degree of master.